A dose-response relationship between exposure to a large-scale HIV preventive intervention and consistent condom use with different sexual partners of female sex workers in southern India - Deering Kathleen N; Boily Marie-Claude; Lowndes Catherine M; Shoveller Jean; Tyndall Mark W; Vickerman Peter; Bradley Jan; Gurav Kaveri; Pickles Michael; Moses Stephen; Ramesh Banadakoppa M; Washington Reynold; et al. (BMC, 2011)
Abstract Background The Avahan Initiative, a large-scale HIV preventive intervention targeted to high-risk populations including female sex workers (FSWs), was initiated in 2003 in six high-prevalence states in India, including Karnataka. This study assessed if intervention exposure was associated with condom use with FSWs' sexual partners, including a dose-response relationship. Methods Data were from a cross-sectional study (2006-07) of 775 FSWs in three districts in Karnataka. Survey methods accounted for the complex cluster sampling design. Bivariate and multivariable logistic regression was used to separately model the relationships between each of five intervention exposure variables and five outcomes for consistent condom use (CCU= always versus frequently/sometimes/never) with different sex partners, including with: all clients; occasional clients; most recent repeat client; most recent non-paying partner; and the husband or cohabiting partner. Linear tests for trends were conducted for three continuous intervention exposure variables. Results FSWs reported highest CCU with all clients (81.7%); CCU was lowest with FSWs' husband or cohabiting partner (9.6%). In multivariable analysis, the odds of CCU with all clients and with occasional clients were 6.3-fold [95% confidence intervals, CIs: 2.8-14.5] and 2.3-fold [95% CIs: 1.4-4.1] higher among FSWs contacted by intervention staff and 4.9-fold [95% CIs: 2.6-9.3] and 2.3-fold [95% CIs: 1.3-4.1] higher among those who ever observed a condom demonstration by staff, respectively, compared to those who had not. A significant dose-response relationship existed between each of these CCU outcomes and increased duration since first contacted by staff (P=0.001; P=0.006) and numbers of condom demonstrations witnessed (P=0.004; P=0.026); a dose-response relationship was also observed between condom use with all clients and number of times contacted by staff (P=0.047). Intervention exposure was not associated with higher odds of CCU with the most recent repeat client, most recent non-paying partner or with the husband or cohabiting partner. Conclusion Study findings suggest that exposure to a large-scale HIV intervention for FSWs was associated with increased CCU with commercial clients. Moreover, there were dose-response relationships between CCU with clients and increased duration since first contacted by staff, times contacted by staff and number of condom demonstrations. Additional program effort is required to increase condom use with non-commercial partners.